PENGOLAHAN LIMBAH AIR KELAPA MENJADI NATA DE COCO OLEH IBU KELOMPOK TANI DI KABUPATEN KUDUS - Fafa Nurdyansyah; Dyah Ayu Widyastuti (Jurnal Kewirausahaan dan Bisnis, 2017)
Coconut water is one of traditional market waste problem. Use ofcoconut fruit remain its water useless then castaway to environment eachday. Its waste problem can be solved with woman empowering especiallyfarmer lady to process coconut water into valueable food product. The aim ofthis program is to solve environmental problem in coconut waste, placed inKudus, by increasing skills of nata de coco making. The program wasperformed by tutorial and practical work of processing coconut water intofood product. The processed nata de coco can be potentially use as superiorfood product at Kudus. Skill increasing of its farmer lady also expected to risehome income and prosperity at Kudus.